Development of tri-layered biomimetic atelocollagen scaffolds with interfaces for osteochondral tissue engineering - Xu, Y (2022)
The development of biomimetic scaffolds for cartilage, calcified cartilage and bone regeneration for precise osteochondral repair remains a challenge. In this study, we used liquid-phase co-synthesis to construct a novel tri-layered scaffold with the top layer containing type II atelocollagen and chondroitin sulphate for cartilage regeneration, the intermediate layer with type II atelocollagen and hydroxyapatite for calcified cartilage formation and the bottom layer with type I atelocollagen and hydroxyapatite for bone growth. The tri-layered scaffold designed in this study is mechanically superior to other tri-layered scaffolds with hard interfaces and has a lower risk of delamination owing to higher cohesion resulting from the interfaces between the layers of the scaffold. In vitro analyses revealed that although monolayered scaffolds stimulated bone marrow stem cells to differentiate and form cartilage, calcified cartilage and bone separately (detected using quantitative PCR analysis and staining with safranin-O and alizarin red S), the tri-layered scaffolds supported the regeneration of cartilage, calcified cartilage and bone simultaneously after 2 and 4 months of implantation (detected using gross and micro-CT imaging, histological staining and Avizo, a three-dimensional reconstruction tool used to detect micro-level defects usually in metals). Therefore, our study presents a promising approach to devising strategies for the precise repair of osteochondral defects.